How ghost scenarios haunt strategy execution - Lang, Trudi; Ramírez, Rafael (MIT Sloan Management Review, 2023)
Executives engaged in strategic planning tend to work with an implicit view of the future that is deeply embedded in their organization's strategy as a set of unquestioned assumptions about the future business context. Leaders need to surface what the authors call ghost scenarios or risk implementing strategies that are ripe for disruption due to changes that planners haven't recognized. The authors offer two case studies and suggest ways leaders can bring these unexamined assumptions into view.
"Reprint #65208.". - Includes bibliographical references
Keywords: Strategic planning